Biodiversidade arbórea e estoque de carbono em áreas verdes urbanas: contribuições para a infraestrutura verde de São Paulo, SP - França, José Ulisses Bezerra de (2017)
The disorderly growth of urban centers has brought a series of social and environmental complications, among them the fragmentation of green areas, the loss of biodiversity and the introduction of exotic and invasive species that directly affect the provision of ecosystem services. Such services are fundamental in urban environments, especially in poorly planned cities, such as the city of São Paulo. Thus, it is fundamental to evaluate the urban green spaces, mainly regarding the composition of species and carbon stock. In this sense, the present master's work investigated the floristic composition of public square trees in the city of São Paulo, as well as the carbon stock associated with this vegetation. Thirteen public squares were selected in four Regional Prefectures belonging to two zones, East and West. All trees with diameter at breast height (DBH) greater than 5 cm were selected and identified by means of collection of the preferentially flowering branch and the DAP and height were measured. They were inventoried 1510 individuals, belonging to 29 botanical families and 91 different species. Of this total, 56.4% were exotic species, 45.3% native and 0.3% undetermined. The most representative botanical family of this study was Fabaceae and in relation to functional groups, 87% of the individuals were trees and only 13% were palm trees. The square with the greatest abundance of species was José Ória and Carlos januário and in general, a positive correlation was observed between the size of the area of the square and abundance of species, however, the size of the area was not correlated (alpha <95%) with other attributes And ecological ecological indexes. However, floristic similarity was found in squares of the same size, with emphasis on the taxonomic family level. It was observed that all the individuals stored a total of 464.9 tons of C, being that this value is equivalent to 65.2 Ton C. ha-1. The exotic species had great contribution in the storage of the element in their respective trunks. Thus, the urban green areas of the present study show a floristic pattern that follows some tendencies of urbanized areas outside the country, due to the scarcity of studies of this nature in Brazil, and they store a reasonable amount of C per hectare of area Sampled, thus providing a great environmental service for the city of São Paulo. Based on these possible results, it is hoped to contribute to proposals and management plans for urban afforestation in the city of São Paulo, especially with regard to the creation of ecological corridors for the transit of urban fauna.